H∞ consensus tracking of recovery system for multiple unmanned underwater vehicles with switching networks and disturbances. (1st February 2022) - Zhang, Wei; Zeng, Jia; Zhang, Jun; Li, Zixuan
Abstract: This study focused on the H∞ consensus tracking of the recovery system of multiple unmanned underwater vehicles (UUVs) with switching networks and disturbances. Considering the complexity of the marine environments, the information communication was described by a switching topology that obeys the Markov chain. A novel H∞ consensus protocol was proposed for the multi-UUV recovery system with switching communication topology and disturbances. By using the Lyapunov–Krasovskii functional and linear matrix inequality, the sufficient conditions for the multi-UUV recovery system to achieve stochastic H∞ consensus were deduced, and based on the above conditions, the controller gain was designed. Finally, three-dimensional simulations of the multi-UUV recovery systems were performed. The simulation results validated the feasibility of the H∞ control strategies. Highlights: The multi-UUV recovery problem with communication constraints is converted into an H∞ consensus tracking problem. An H∞ consensus protocol with the Markov switching networks and time delay for a multi-UUV recovery system is proposed. The H∞ consensus controller gain was designed such that multiple UUVs finally reach the state consistent with the mothership.